(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article presents methods of using various energy sources in the construction processes of buildings in the conditions of modern Uzbekistan. In the article, energy sources are the types of them, buildings are being constructed in the process of using the main differences, advantages and disadvantages given.